Evaluation of Recurrence of Ischemic Stroke and Transient Ischemic Attack Three Months After the First Transient Ischemic Attack Based On Diffusion-Weighted Imaging (DWI) - Abolfazl Atalu; Firouz Amani; Kiana Kheirkhah (Patient Safety and Quality Improvement Journal)
Introduction: One type of stroke is the Transient Ischemic Attack (TIA) which lasts less than twenty-four hours; of all patients, about 10 percent develop a stroke within three months after the first symptoms, and 30 percent develop over five years. Imaging is needed for differential diagnosis of this type of stroke. This study aimed to evaluate the recurrence of ischemic stroke and TIA three months after the first transient ischemic attack based on DWI results.Materials and Methods: This cross-sectional study was done on 135 TIA patients referred to Alavi Hospital in Ardabil City. All patients were examined at admission time by DWI imaging and laboratory tests and followed up three months later by phone and hospitalization, and necessary information was collected by a checklist.Results: The average ABCD2 score in people with and without recurrence was 4.69 and 4.02, respectively. Also, the mean ABCD2 score in individuals with abnormal DWI was significantly higher than in individuals with normal DWI (4.72 vs. 4.04, p=0.001). After the first TIA attack, patients with abnormal DWIs had a significantly higher recurrence of TIA and stroke in the first 90 days. Conclusion: This study showed that TIA‌ patients with higher ABCD2 scores in the first 24 hours based on DWI are more likely to have a recurrence of TIA or the onset of stroke within 90 days.